Ultrahigh field brain magnetic resonance imaging using semiadiabatic radiofrequency pulses. (30th December 2021) - Ordidge, Roger; Blunck, Yasmin; Glarin, Rebecca; Moffat, Bradford; Johnston, Leigh
Abstract : Great attention is being paid to solving, or mitigating, the technical problems associated with MRI at ultrahigh field strengths of 7 T and higher. This paper explores the use of the semiadiabatic spin‐echo (SA‐SE) pulse sequence, which uses semiadiabatic radiofrequency (RF) pulses to remove and/or mitigate the effects of the nonuniform B1 excitation field and B0 inhomogeneity associated with the electromagnetic properties of the human brain. A semiadiabatic RF pulse version of the recently published serial transmit excitation pulse (STEP) RF pulse sequence is also presented that now incorporates semiadiabatic pulses, henceforth is called SA‐STEP. As demonstrated by computer simulation, and confirmed using head imaging, both techniques can produce multislice SE MR imaging at 7 T. These new methods use relatively low RF power and achieve good coverage of the human brain in a single scan. Abstract : This paper explores the use of semiadiabatic (SA) and STEP RF pulses to remove and/or mitigate the effects of nonuniform B1 excitation field and B0 nonuniformities associated with human brain imaging at high fields. The figure shows a plot of simulated spin‐echo (SE) image slice signal versus B1 amplitude for sinc, SA‐SE, and new SA‐STEP sequences, demonstrating better tolerance to B1 nonuniformity (B1 = 1.0 corresponds to nominal 90 0 excitation). Applications to human brain imaging at 7 T are presented and evaluated.